Primo Levi and the Terrestrial Condition (ENTHYMEMA, 2023)
In his stories, Primo Levi presents contrasting planetary visions of Earth: one depicting it as an expanding technosphere made of entangled beings, and the other as a world of disparities impacted by the agency of a mutated humanity. But Levi's ideas of planet do not solely advocate for a utopian cosmopolitanism of all living beings; he critically probes the tension between technology's promises in industrialized societies and the worldview that sees Earth merely as an exploitable resource. Moreover, his stories emphasize the divisions and the contradictions created by the planetarization of the logic of industrial modernity. This essay analyzes selected short stories from Vizio di forma, seeking to unpack Levi's intricate engagements with planetary concepts and the emergent idea of a terrestrial condition. Central to this exploration is how Levi's planetary vision reflects the inherent tensions between the individual and the collective, and between different scales and ways of existing.
Keywords: Planetarity; Primo Levi's Science Fiction; Planetary Turn; Anthropocene; Gaia